University Ruin and the Contested Usefulness of the Humanities in Japanese Higher Education - Ito, Toshiko (Forum Pedagogiczne, 2019)
At Japanese universities, the standing of the humanities has declined considerably over the last two decades. This decline is reminiscent of Bill Readings’ account of American universities as articulated in his University in Ruins (1996). In Readings’ analysis, American universities are ‘ruined’ because they have abandoned their intrinsic cultural mission in a shift that greatly undermines the standing of the humanities. His recommendation in the American context of the time is the adoption of a certain rhythm of disciplinary attachment and detachment, such as giving more weight to short-term collaborative projects on the assumption that every collaboration has a certain half-life. The manner in which Japanese universities are dealing with the shift against the humanities is more complex than Readings’ recommendation. While the government’s policy makers favor short-term usefulness in a sense superficially similar to Readings’ recommendation, scholars in the humanities tend to insist that the usefulness of humanities is undeniable but needs to be evaluated on a longer timescale.